Role Of Seasonal Variation On The Prevalence And Risk Factors Of Trichuriasis Among The Aboriginal Community In Malaysia - S. A. Noradilah; T. S. Anuar; I. L. Lee (Sciendo, 2024)
Indexed by WOS/SCOPUS/ERA